Aerobic Interval Training Impacts Muscle and Brain Oxygenation Responses to Incremental Exercise - Caen, Kevin; Vermeire, Kobe; Pogliaghi, Silvia; Moerman, Annelies; Niemeijer, Victor; Bourgois, Jan Gustaaf; Boone, Jan (Frontiers in Physiology, 2019)
The purpose of the present study was to assess the effects of aerobic interval training on muscle and brain oxygenation to incremental ramp exercise. Eleven physically active subjects performed a 6-week interval training period, proceeded and followed by an incremental ramp exercise to exhaustion (25W.min-1). Throughout the tests pulmonary gas exchange and muscle (Vastus Lateralis) and brain (prefrontal cortex) oxygenation (concentration of deoxygenated and oxygenated haemoglobin, HHb and O2Hb, and tissue oxygenation index, TOI) were continuously recorded. Following the training intervention V ̇O2peak had increased with 7.8±5.0% (P<0.001). The slope of the decrease in muscle TOI had decreased (P=0.017) 16.6±6.4% and the amplitude of muscle HHb and totHb had increased (P<0.001) 40.4±15.8% and 125.3±43.1%, respectively. The amplitude of brain O2Hb and totHb had increased (P<0.05) 40.1±18.7 and 26.8±13.6%, respectively. The training intervention shifted breakpoints in muscle HHb, totHb and TOI, and brain O2Hb, HHb, totHb and TOI to a higher absolute work rate and V ̇O2 (P<0.05). The relative (in %) change in V ̇O2peak was significantly correlated to relative (in %) change slope of muscle TOI (r=0.69,P=0.011) and amplitude of muscle HHb (r=0.72,P=0.003) and totHb (r=0.52,P=0.021), but not to changes in brain oxygenation. These results indicate that interval training affects both muscle and brain oxygenation, coinciding with an increase in aerobic fitness (i.e.,V ̇O2peak). The relation between the change in V ̇O2peak and muscle but not brain oxygenation suggests that brain oxygenation per se is not a primary factor limiting exercise tolerance during incremental exercise.